PENGARUH KEPEMIMPINAN DAN DISIPLIN TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR KEMENTERIAN AGAMA KABUPATEN TULANG BAWANG - Dharmawan Dharmawan (Derivatif : Jurnal Manajemen, 2017)
Formulation of the problem in this study is whether there is a significant effect of leadership on the performance of employees, whether there is influence of labor discipline significantly to the work performance of employees, whether there is influence leadership style and discipline significant work on the performance of employees on the Office of Religious Affairs Tulang Bawang.Relevant to the formulation of the problem, the purpose of this study was to analyze the influence of leadership style on job performance of employees, to analyze the impact of discipline on work performance of employees, to analyze the influence of leadership style and discipline of work together on job performance of employees on the Office of Religious Affairs Tulang Bawang.The hypothesis of this study is the leadership style have a significant effect on the performance of employees, labor discipline significant effect on the performance of employees, leadership style and discipline together/simultaneous significant effect on the performance Office of Religious Affairs Tulang Bawang.Data were collected by questionnaires, interviews, observation and study dokumentasi. Variabel studied with Likert scale. Data processing using SPSS version 16 software, analyzed by qualitative and quantitative analysis, and hypothesis testing of correlation with the number of respondents 34 people.The results showed that: a significant difference between leadership style on job performance of employees, a significant difference between the discipline of work on the performance of employees, a significant difference between the style of leadership and discipline together/simultaneously on the performance of employees of the Office of Religious Affairs Tulang Bawang. And the effect is more dominant leadership style affects job performance of employees Office of Religious Affairs Tulang Bawang. Keywords: Leadership, Discipline and Job Performance